Effects of frequency drift and harmonics in power factor correction systems - López-Leyva, Josué Aarón; Ponce Camacho, Miguel Ángel; Mejía, E.A.; Estrada, J.; Ramos García, V.M. (My University, 2019)
This paper shows the effect of the harmonics signals and frequency drift in the power factor correction systems. The phase induced concept is introduced as a key to understanding the dynamics of the power factor parameter. Results shown are related to real and reactive power considering the four first harmonics signal in an electrical network with a nominal frequency at 60 Hz. In addition, the bandwidth for correct the phase induced by harmonics is proposed based on integration time uses for analysis the frequency drift.
Keywords: Harmonic analysis; Reactive power; Time-frequency analysis; Power harmonic filters; Monitoring; Frequency control; Campus Ensenada